TRANSLATION STRATEGIES FOR INFORMATION TECHNOLOGY TERMS IN MULTIMODAL DISCOURSE (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The rapid development of digital technologies has significantly influenced the formation, translation, and representation of information technology terminology. In contemporary digital environments, IT terms are not presented only through verbal language, but also through icons, symbols, buttons, colors, and interface layouts. This article investigates the translation strategies used for information technology terms in multimodal discourse, with particular attention to English IT terms and their Uzbek equivalents. The study is based on a corpus of frequently used IT terms collected from websites, mobile applications, operating systems, and artificial intelligence platforms. Using multimodal discourse analysis, comparative analysis, translation analysis, and visual semiotic analysis, the article identifies the main strategies applied in translating IT terminology: direct equivalence, transliteration, calque, descriptive translation, functional translation, metaphorical translation, and adaptation. The findings show that the translation of IT terms in multimodal discourse depends not only on lexical equivalence, but also on the interaction between verbal and visual elements. The results reveal that functional translation and direct equivalence are among the most productive strategies, while visual signs play an important role in clarifying meaning, reducing ambiguity, and facilitating user comprehension. The article concludes that multimodal compatibility should be considered an essential criterion in the translation of IT terminology.
Keywords: information technology terms, multimodal discourse, translation strategy, visual-verbal integration, digital interface, English, Uzbek.